Acceptability of e-training to support dentists to discuss tooth-kind behaviours with parents: Presenter(s): Sarah Peters, University of Manchester, United Kingdom. (April 2023) - Goldthorpe, Joanna; Kilbee, Lauren; Cotterill, Sarah; Hart, Joanne; Pretty, Iain
Abstract : Background: Tooth decay is preventable, through health behaviours (e.g. tooth brushing and limiting sugar consumption). However, in the UK, the most common reason for hospital admission in young children is to have decayed teeth removed under general anaesthetic. Dentists report finding behaviour change conversations challenging, and often use approaches known to be ineffective in changing behaviours (e.g. information giving, fear tactics). The study aim was to investigate the acceptability of a health psychology-informed behaviour change communication toolkit. Method: A brief, interactive online training course was developed and made available to a sample of 117 dentists, trainees and allied practitioners. At baseline and post-training, participants completed questionnaires of knowledge, motivation, and confidence in holding behaviour change conversations. In-depth interviews were conducted with a purposive sample of 16 practitioners to investigate how the intervention could be developed in the context of COVID-19, which has severely disrupted routine dental services. Findings: Participants valued the training, which they described as novel and provided them with new strategies to enhance behaviour change conversations. Post-training questionnaires indicated participants felt more confident after training, with increased knowledge around planning and initiating behaviour change conversations with families. Early years practitioners working in a variety of non-dental settings (e.g. nurseries and children's centres) reported opportunities to have behaviour change conversations with parents, and welcomed further tailoring of the online training to help them capitalise on these interactions within these settings. Discussion: Dental and non-dental practitioners are similarly motivated to have conversations with parents about improving their oral health. Brief online training can improve their capability to initiate these conversations in ways that do not damage the therapeutic relationship. To recover oral health services beyond COVID-19, there is potential for professionals working with parents in non-dental settings to develop skills in oral health promotion.